Association of job stress, CLOCK gene polymorphism and their interaction with poor sleep quality - Li, Yuling; Cao, Zeyuan; Wu, Shuang; Wang, Chao; He, Shuchang; Dong, Yan; Zhang, Xiangyang (Journal of sleep research, 2021)
Job stress and the Circadian Locomotor Output Cycles Kaput (CLOCK) gene could affect circadian rhythm and sleep quality. The main aim of our present study was to investigate the association of job stress, CLOCK gene polymorphism and their interaction with sleep quality in a non‐clinical Chinese Han population, which has not been reported to date. Using a cross‐sectional design, 450 subjects were recruited in Beijing. Sleep quality was measured with the Pittsburgh Sleep Quality Index (PSQI) and job stress was measured with the Work Stress Scale. CLOCK gene rs11932595 polymorphism was genotyped in 297 blood samples. Correlation analysis showed a close but different association of high job stress with the PSQI and its components. Analysis of variance showed significant main effects of the CLOCK gene rs11932595 polymorphism. G‐allele carriers had a higher score in the PSQI, sleep duration, sleep latency and sleep disturbances. Further interaction analyses showed an ordinal interaction on sleep duration, and a disordinal interaction on daytime dysfunction. Specifically, G‐allele carriers had poorer sleep duration than AA homozygotes when in high job stress, while the two subgroups displayed similar sleep duration when in low job stress, conforming to the diathesis–stress model. In comparison to G‐allele carriers, AA homozygotes experienced less daytime dysfunction when in low job stress whereas more daytime dysfunction when in high job stress, fitting with the differential susceptibility model. As genetic links have been revealed, our investigation might be conducive for elucidating aetiological factors for sleep quality and targets for implementing interventions to attain good sleep quality.